Can Financial Rewards Increase the Interest of a Student Career in the Field of Education Accounting? - Sari, Ayu Ketut Rencana; Wahyuni, Made Arie (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2023)
The goal of this study was to identify the characteristics that affect accounting students' interest in selecting a career as an accountant educator, with the moderating variables of intrinsic worth of the work, professional recognition, and financial benefits. Students at the Ganesha University of Education's Accounting Study Program made up the study's sample. 166 respondents made up the sample in a simple random sampling approach. The data is shared online via a Google form, after which the SmartPLS program processes it. Partially, this study shows that the intrinsic value of work does not affect the career interest of students in the field of accounting educators, while professional recognition partially has a positive and significant effect on career interests of students in the field of accounting educators. Financial awards are also able to moderate the effect of professional recognition on students' career interests in the field of accounting educators.